EP212/#1141 Clinical and genomic landscape of ovarian clear cell carcinoma. (4th December 2022) - Cai, Hongbing; Dai, Mengyuan; Shi, Yuying; Ye, Hong; Wu, Si-Si; Yuan, Guangwen; Wu, Lingying
Abstract : Objectives: The genetic landscape of Ovarian clear cell carcinoma (OCCC) is poorly described. We sought to identify genomic characterization of OCCC and correlate findings with clinical outcomes. Methods: We performed a multi-center prospective clinical sequencing program of OCCC patients (n=95) using tumor-normal massively parallel sequencing that included 688 cancer-related genes, and comprehensively analyze the clinical and genomic characteristics of OCCC. Results: In the 95 samples, the most frequently mutated genes were ARID1A(61.1%), PIK3CA(61.1%), TP53(24.2%), MUC16(22.1%), KMT2C(20%). KMT2C, MECOM, SMARCA4, PDGFRB and CDC27 were significantly related to platinum resistance (P<0.05). The Progression-free survival (PFS) was shorter among patients with tumors harboring ARID2, CDKN2A, CUL4A, DAXX and DDR1 mutations (P<0.05) compared to patients without these mutations. The overall survival (OS) was significantly shorter among patients harboring CASP8, IDH2, LZTR1, MDM4 and PI3KR2 mutations (P<0.05). The OS was longer among patients with tumors harboring RYR2 (P<0.05) and driver gene POLE (P<0.05) mutations. Patients with POLE mutation showed extremely high TMB. An increasing trend of CD8+ cytotoxic T lymphocytes (CTL) (P<0.05) in POLE mutation was observed compared with POLE wild-type in immunohistochemical multiplex analysis. Immunohistochemistry detection revealed about 15.8% of patients had decreased mismatch repair (MMR) expression. Conclusions: Our study revealed the correlation of the characteristics of somatic mutations in OCCC with its clinical outcomes, and identified high-frequency mutated genes related to prognosis, recurrence and platinum resistance, which provided important implications for future molecular diagnosis and targeted therapy for OCCC.